TANGGUNG JAWAB DIREKSI DALAM MENJALANKAN CSR (CORPORATE SOCIAL RESPONSIBILITY) BERDASARKAN PERATURAN PEMERINTAH NOMOR 47 TAHUN 2012 - STEPHEN RICHARDO; BISMAR NASUTION; WINDHA WINDHA (Universitas Sumatera Utara, 2013)
As a legal subject who support the rights and obligations, one of the Corporate obligations as set forth in the Limited Liability Company Act and Rule The exercise is about social responsibility. The main issues to be discussed in this paper include how the implementation of CSR in Indonesia, how the legal responsibilities of directors and CSR according Limited Liability Company Law No. 40 of 2007 and how the responsibilities of directors in implementing CSR according to Government Regulation No. 47 Year 2012. This writing applies method of normative legal research with data collection Library Studies (Researh Library), by examining library materials or secondary data form the primary legal materials relevant regulations, secondary legal materials related documents and legal materials tertiary which is a clue to primary and secondary legal materials. Secondary data has been compiled is then analyzed using deductive and inductive methods to obtain conclusions. The conclusion of this paper is the implementation of Corporate Social Responsibility (CSR) in Indonesia is based on the Limited Liability Companies Act No. 40 of 2007 and Government Regulation No. 47 Year 2012 and legislation related. The legal relationship between responsibility and CSR directors pursuant to the Limited Liability Companies Act No. 40 of 2007 is the director responsible for the management and maintenance of the company as well as in the implementation of CSR as mandated by Article 74 of the Limited Liability Company Act. Responsibilities of directors in carrying out CSR according to Government Regulation No. 47 Year 2012 is that CSR is the responsibility of the directors, organ company which has overall responsibility for the management company, and has the authority to represent the company, to be followed with respect to the annual work plan and the appropriateness and reasonableness and reporting. Kata Kunci : Tanggung Jawab, Direksi, dan Corporate Social Responsibility.